Сlinical results of surgical treatment of patients with parasagittal meningiomas operated with the help of infred laser - V. V. Stupak; S. V. Chernov; A. P. Maiorov; S. G. Struts (Бюллетень сибирской медицины, 2008)
Despite a significant advance in microsurgery of the parasagittal brain meningiomas the problem of its surgical treatment is not closed at the present time. This is due to the fact that parasagittal meningiomas can ingrow to the sinus lumen. In this cases the possibility of tumor resection using conventional techniques is limited. Attempts at the tumor radical removal lead to a massive operating blood loss, a stable severe neurological deficit and decrease the quality of life. This results in high recurrence rate of parasagittal meningiomas also. The paper presents the results of ND-YAG laser use in the removal of parasagittal meningiomas with assessment of its application efficacy as compared with conventional techniques.